The polyphenol quercetin protects the mev‐1 mutant of Caenorhabditis elegans from glucose‐induced reduction of survival under heat‐stress depending on SIR‐2.1, DAF‐12, and proteasomal activity. Issue 5 (10th January 2014) - Fitzenberger, Elena; Deusing, Dorothé J.; Marx, Carolin; Boll, Michael; Lüersen, Kai; Wenzel, Uwe
<x xml:space="preserve">Abstract</x> Scope Hyperglycemia is a hallmark of diabetes mellitus but slighter increases of blood glucose levels are observed also during ageing. Using the Caenorhabditis elegans mev‐1 mutant, we identified molecular mechanisms underlying the protection from glucose toxicity by the polyphenol quercetin. Methods and results We fed C. elegans mev‐1 mutants on a liquid medium supplemented with 10 mM glucose, which resulted in a reduced survival at 37°C. The polyphenol quercetin (1 μM) was able to prevent glucose‐induced lifespan reduction completely. RNA interference revealed that the sirtuin SIR‐2.1, the nuclear hormone receptor DAF‐12, and its putative co‐activator MDT‐15 were critical for the quercetin effects. Moreover, RNA interference for key factors of proteostasis reduced survival, which was not further affected by glucose or quercetin, suggesting that those proteins are a target for both substances. Besides unfolded protein response, proper functionality of the proteasome was shown to be crucial for the survival enhancing effects of quercetin and the polyphenol was finally demonstrated to activate proteasomal degradation. Conclusion Our studies demonstrate that lowest concentrations of quercetin prevent a glucose‐induced reduction of survival. SIR‐2.1, DAF‐12, and MDT‐15 were identified as targets that activate unfolded protein response and proteasomal degradation to limit the accumulation of functionally restricted proteins.